International Journal of Environment: One of the fast growing journals of NepJOL - Bhandari, Govinda (International Journal of Environment, 2015)
DOI: http://dx.doi.org/10.3126/ije.v4i2.12668 International Journal of Environment Vol.4(2) 2015: i-ii